Education Game Kit "Princess Stick and Color Sword" For Preschooler by Using Tcs3200 Color Censor and Arduino Nano - Dwi Ratnawati; Vivianti Vivianti (International Journal of Applied Business and Information Systems, 2019)
Introducing and teaching color is one of the important parts in learning in childhood period. One of the learning color methods that effective enough is identifying color from the concrete things in the environment with parent assistance to mention the color object. it becomes a limitation when children usually want to play and explore. This research aims to create a toy product which can be used as color learning media for children by still interacting with their environment. Therefore, the researchers will create toy products in the shape of sword and princess stick that can identify object color and produce voice based on the object. Voice output can be selected in Indonesian and English. The main program of this system is identifying object color and audio reading of object color that placed closed to the toy using TCS3200 color censor and Arduino Nano.